The effect of CO on the transformation of arsenic species: A quantum chemistry study - Anthony, Edward J.; Zou, Chan (Elsevier, 2020)
To explore the effect of CO on the transformation of arsenic species, the reaction mechanism of homogeneous and heterogeneous reactions for arsenic oxides (AsO2 and As2O3) with CO were investigated via density functional theory (DFT). The geometries of reactants, intermediates, transition states and products for each reaction were optimized by using the B3LYP method in conjunction with the 6-31G(d) basis set, and the single-point energy of each structure was calculated at the B2PLYP/Def2-TZVP level. Also, thermodynamic and kinetic analyses were conducted to determine the reaction process. The results showed that the homogeneous reaction of AsO2 and CO has two channels and a transition state is found in each case. The homogeneous reaction process of As2O3 and CO undergoes two transition states and, finally, As2O3 is reduced to sub-oxides by CO. Char has a strong adsorption affinity for AsO2 and As2O3 in the presence of CO, and the adsorption mode of the AsO2 molecule on the char surface has a great influence on its reduction. The activation energy of the homogeneous reduction of As2O3 (75.9 kJ·mol-1) is lower than the heterogeneous reduction (94.2 kJ·mol-1), which suggests that As2O3 is more likely to react with CO in the flue gas. The calculation results revealed the mechanism for the influence of CO on arsenic behavior by density functional theory. These results are helpful for a molecular-level understanding of the transformation of arsenic species, which in turn provides a theoretical foundation for the emission and control of arsenic.
Keywords: CO; transformation of arsenic species; thermodynamic; density functional theory; kinetic